Proceedings of SPE/ICoTA Coiled Tubing Conference and Exhibition 2002
DOI: 10.2523/74811-ms
|View full text |Cite
|
Sign up to set email alerts
|

Flow Behavior of Fracturing Slurries in Coiled Tubing

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractHydraulic fracturing through coiled tubing (CT) has become an effective and economical stimulation technique for wells with multiple zones to be fractured. Yet, prediction of friction pressure losses of fracturing slurries in coiled tubing presents a unique challenge in the fracturing job design.This paper presents an experimental study of friction pressure losses of fracturing slurries in coiled tubing using a full-scale coiled tubing test loop which consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Meanwhile, researches on fracture initiation and extension [5] as well as theories referring to annulus injection were conducted [6][7]. During the application in horizontal well, the coordination problems on hyrajet fracturing technology and coiled tubing arise, involving coiled tubing optimum design, tubing erosive mechanism of proppant and pipe safety etc [8][9][10]. However, researches on the inner jet flow field, quantitative research and influence factor analysis on boost pressure were rarely mentioned in related researching documents.…”
Section: Introductionmentioning
confidence: 97%
“…Meanwhile, researches on fracture initiation and extension [5] as well as theories referring to annulus injection were conducted [6][7]. During the application in horizontal well, the coordination problems on hyrajet fracturing technology and coiled tubing arise, involving coiled tubing optimum design, tubing erosive mechanism of proppant and pipe safety etc [8][9][10]. However, researches on the inner jet flow field, quantitative research and influence factor analysis on boost pressure were rarely mentioned in related researching documents.…”
Section: Introductionmentioning
confidence: 97%
“…Ogugbue and Shah [12] presented the results of an experimental study carried out to investigate frictional pressure losses behavior of drag reducing polymer solutions, flowing turbulently through an eccentric annulus. Shah et al [13] and Shah [14] studied the impact of containing sand on friction pressure losses of fracturing fluid and drilling fluid. Properties of drilling fluid affected the friction pressure losses observably, it was found that drill cuttings in drilling fluid can significantly increase friction pressure losses of fluid in CT, and the higher the flow rate is, the more significantly the friction losses increase.…”
Section: Introductionmentioning
confidence: 99%